Implementasi Teori Perkembangan Kognitif Jean Piaget Pada Anak Usia Dini - Khusnul Khotimah; Agustini Agustini (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Jean Piaget's theory of cognitive development is one theory that explains how children adapt to the environment and interpret objects and events around them. Piaget stated that children's intelligence or cognitive abilities change and progress through four stages. While early childhood development is the progress experienced by children as a whole, both in terms of physical to emotional development. The purpose of this study was to determine the theory of cognitive development that occurs in early childhood. Both in the form of understanding cognitive development, factors that influence children's cognitive development, stages in children's cognitive development, children's cognitive development methods, appropriate education for early childhood and developmental theory in early childhood. In this study, the author uses a library research approach or literature study. To find data on literacy studies, you can refer to books, research journals, scientific papers, and published articles. From this study, the results of the theory of cognitive development are related to involving understanding based on knowledge that seems real and comes from experience. And the most appropriate learning applied in early childhood education is the student center model. The student center learning method is a child or student-centered learning model.